(untitled) (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to evaluate the diuretic activity of Eysenhardtia polystachya bark aqueous extract at different doses in a rat model. Different doses of E. polystachya (125, 250, 500 and 750 mg/kg body weight), furosemide (4 mg/kg) and vehicle were administered per os to female rats (n=6 animals per group). After 6 hours in metabolic cages, the effect on urinary flow, glomerular ?ltration rate and electrolyte balance of sodium and potassium were assessed in all animals. E. polystachya at the doses of 500 and 750 mg/kg induced diuretic activity, since markedly increased (p<0.05) the urinary flow rate, similar to that of furosemide treated group. Only the dose of 750 mg/kg produced an increment in urinary excretion of sodium but not of potassium compared with control group. These findings indicate that E. polystachya bark-induced diuretic activity, providing evidence for its folkloric use.